1980
DOI: 10.1080/00288233.1980.10417865
|View full text |Cite
|
Sign up to set email alerts
|

Responses to abomasal infusions of casein plus methionine in lactating ewes fed fresh pasture

Abstract: Twin-bearing Romney ewes were fed fresh pasture of 80% organic matter digestibility (11.4 MJ ME per kg OM) and 3.5% N ad libitum for 6 weeks during early lactation. Eight of the 18 ewes were given a daily abomasal infusion of 95 g sodium caseinate and 2 g I-methionine. Voluntary pasture OM intake did not significantly differ between control and infused ewes. The infusions had no effect on milk secretion at peak lactation (week I), but the decline in net rates of protein and fat secretion as lactation progresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
1

Year Published

1983
1983
1996
1996

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 14 publications
2
7
0
1
Order By: Relevance
“…In response to postruminal casein infusions, jugular vein plasma somatostatin concentrations were decreased in nonlactating sheep (Barry et al, 1982) and increased in lactating ewes (Barry, 1980). The portal and hepatic SLI flux measurements (Table 2) were highIy variable, as noted previously in beef steers (Reynolds et al, 1986) and in dairy cows .…”
Section: Discussionsupporting
confidence: 55%
“…In response to postruminal casein infusions, jugular vein plasma somatostatin concentrations were decreased in nonlactating sheep (Barry et al, 1982) and increased in lactating ewes (Barry, 1980). The portal and hepatic SLI flux measurements (Table 2) were highIy variable, as noted previously in beef steers (Reynolds et al, 1986) and in dairy cows .…”
Section: Discussionsupporting
confidence: 55%
“…Heat exposure did not cause an increase in prolactin concentrations beyond that already achieved by continuous lighting. The observed concentrations were within the range (100-280 p.g/l) that has been reported for lactating ewes (Barry 1980;Gow et al 1983).…”
Section: Mild Heat Exposuresupporting
confidence: 80%
“…Few studies in ruminants have examined changes in somatostatin concentration with postruminal nutrient infusion. Jugular vein plasma somatostatin concentrations were decreased in nonlactating ewes (Barry et al, 1982) and increased in lactating ewes (Barry, 1980), and no change was reported in beef steers (Guerino et al, 1991) infused postruminally with casein. However, to our knowledge no studies have measured somatostatin concentration with carbohydrate feeding or infusion in ruminants.…”
Section: Discussionmentioning
confidence: 99%